2016
DOI: 10.1515/cerce-2016-0036
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Rice Grain is Influenced by Organic and Inorganic Sources of Nutrients and Antioxidant Application

Abstract: The present research was conducted to study the influence of organic and inorganic sources of nutrients as well as antioxidant on rice quality. The experiment was designed in split-split plots with four replications, where main plots were assigned to nitrogen (0, 55, 110 and 165 kg N ha−1) and sub plots were allocated to compost (0, 3.5 and 7 tons ha−1), while the sub-sub plots were assigned to ascobien (control, spraying with ascobien in two times at 15 and 30 days after transplanting (DAT), spraying with asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
3
2
0
Order By: Relevance
“…However, the ash and protein content of inorganic rice is higher than those of organic rice for both varieties. Those results are in line with Bagchi et al (2016), Gangmei & George (2017), Gharieb, Metwally, Abou-Khadrah, Glela, & El Sabagh (2017), and Paule, Gomez, Juliano, & Coffman (1979), as inorganic rice has a softer kernel and lower phenol and carbohydrate content, while organic rice has lower ash and protein contents. Ingver, Tamm, & Tamm (2008) reported that inorganic barley and wheat have larger seeds and higher protein contents compared with organic grains.…”
Section: Resultssupporting
confidence: 83%
“…However, the ash and protein content of inorganic rice is higher than those of organic rice for both varieties. Those results are in line with Bagchi et al (2016), Gangmei & George (2017), Gharieb, Metwally, Abou-Khadrah, Glela, & El Sabagh (2017), and Paule, Gomez, Juliano, & Coffman (1979), as inorganic rice has a softer kernel and lower phenol and carbohydrate content, while organic rice has lower ash and protein contents. Ingver, Tamm, & Tamm (2008) reported that inorganic barley and wheat have larger seeds and higher protein contents compared with organic grains.…”
Section: Resultssupporting
confidence: 83%
“…the number of panicles per plant, filled grains percentage and the number of grains per panicle. Similar trend was found by Metwally et al, (2011), Gharieb et al, (2016), Sudhakar et al, (2018) and Ramesh, (2019. Uddin et al, (2013) found that, NPK application resulted in increasing photosynthetic efficiency as well as translocation of assimilates which reflected in increases in most of grain yield components.…”
Section: Grain Yield (T Ha -1 )supporting
confidence: 88%
“…Rice straw contained less total N and higher C:N ratio than compost and farm yard manure (Table 3). Similar trends were obtained by Ahmed and Naeem (2012), Metwally (2015), Gharieb et al, (2016), Halder et al, (2020), Qaswar et al, (2020 and Sahu et al, (2020). Means of each factor designated by the same latter are not significantly different at 5% level using Duncan's Multiple Range Test.…”
Section: Grain Yield (T Ha -1 )supporting
confidence: 79%
“…While a positive relationship between amount of irrigation water and grain yield at different Farmyard manure (FYM) treatments under drought stress condition, indicating that FYM in combination with amount of irrigation help to survive plants under deficit water stress condition (Abd El-Wahed et al, 2015). Organic fertilizers might play an important role to solve environmental pollution problems that caused by agroindustrial wastes (Preap et al,2002 ;Gharieb et al , 2016).The combined chemical and poultry manure fertilization (50:50) produced the maximum yield and its traits of maize (Nasim et al (2012). According to Azab (2016) application of half rate of the chemical NPK combined with bio-fertilizers was effective and logic to achieve the maximum productivity under the condition of investigation in maize.…”
Section: Approaches For Enhancing the Productivity Of Maizementioning
confidence: 99%